The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2006
DOI: 10.1111/j.1365-2427.2006.01590.x
|View full text |Cite
|
Sign up to set email alerts
|

Habitat selection in spatially heterogeneous environments: a test of foraging behaviour in the clonal submerged macrophyte Vallisneria spiralis

Abstract: 1. To test whether clonal macrophytes can select favourable habitats in heterogeneous environments, clonal fragments of the stoloniferous submerged macrophyte Vallisneria spiralis were subjected to conditions in which light intensity and substratum nutrients were patchily distributed. The allocation of biomass accumulation and ramet production of clones to the different patches was examined. 2. The proportion of both biomass and ramet number of clones allocated to rich patches was significantly higher than in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
31
1

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(35 citation statements)
references
References 36 publications
3
31
1
Order By: Relevance
“…Indeed, a CO 2 increase of 2 to 10 times the ambient level was previously shown to promote biomass accumulation of submerged macrophytes in multiple previous studies at various pH levels (Titus 1992, Olesen & Madsen 2000, Yan et al 2006, Malheiro et al 2013. Clonal reproduction is the major reproduction and dispersal method of Vallisneria species (Xiao et al 2006(Xiao et al , 2007a(Xiao et al , 2011. In the present study, longer creeping stems and a greater ramet number were observed under elevated CO 2 conditions, which is consistent with previous studies; this clonal growth enables Vallis neria species to occupy more habitats (Yan et al 2006).…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, a CO 2 increase of 2 to 10 times the ambient level was previously shown to promote biomass accumulation of submerged macrophytes in multiple previous studies at various pH levels (Titus 1992, Olesen & Madsen 2000, Yan et al 2006, Malheiro et al 2013. Clonal reproduction is the major reproduction and dispersal method of Vallisneria species (Xiao et al 2006(Xiao et al , 2007a(Xiao et al , 2011. In the present study, longer creeping stems and a greater ramet number were observed under elevated CO 2 conditions, which is consistent with previous studies; this clonal growth enables Vallis neria species to occupy more habitats (Yan et al 2006).…”
Section: Discussionsupporting
confidence: 82%
“…When inorganic carbon is no longer a limiting factor, nutrient intake will likely be more important than photosynthesis as a result of carbohydrate production, and roots may therefore be emphasized over leaves (Titus & An dorfer 1996, Geng et al 2004). Additionally, greater resource allocation to creeping stems may allow V. natans to capture more resources, and reduce competition for soil nutrients with neighboring plants (Xiao et al 2006, 2007a, Yan et al 2006, and more buds will likely lead to higher productivity in waters with high CO 2 concentrations.…”
Section: Discussionmentioning
confidence: 99%
“…The effect of sediment nutrients on the growth of submerged macrophytes has received increasing attention during the past decade (Smith et al 2002, Hangelbroek et al 2003, Xiao et al 2006, Wang & Yu 2007. Variations in the response of plants to sediment nutrient levels have been reported for plant size (Xie & Yu 2011a), biomass and resource allocation , plastic adjustments (Mony et al 2007), root structure (Xie et al 2007), and reproductive strategy (Xiao et al 2006). Even small variations in nutrient availability can cuase large differences in plant growth and morphological responses (Sugiyama & Bazzaz 1998, Müller et al 2000.…”
Section: Introductionmentioning
confidence: 99%
“…Sediment is the primary source from which most submerged macrophytes take up macro-and microelements (Barko & Smart 1983, Barko & Smart 1986, although submerged macrophytes can take up nutrient ions from the water column in some eutrophic cases (Madsen & Cedergreen 2002). The effect of sediment nutrients on the growth of submerged macrophytes has received increasing attention during the past decade (Smith et al 2002, Hangelbroek et al 2003, Xiao et al 2006, Wang & Yu 2007. Variations in the response of plants to sediment nutrient levels have been reported for plant size (Xie & Yu 2011a), biomass and resource allocation , plastic adjustments (Mony et al 2007), root structure (Xie et al 2007), and reproductive strategy (Xiao et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, much of the research dedicated to understanding the relationship between sediment nutrients and reproductive output has focused on sexual reproduction. Although the influence of sediment nutrients on clonal plants has begun to receive attention, we do not have a thorough understanding of asexual propagation, particularly for plants in aquatic habitats (Slade & Hutchings 1987, Dong et al 1997, Hangelbroek et al 2003, Xiao et al 2006. Asexual reproduction is generally assumed to be more common in aquatic habitats than in terrestrial habitats because of unfavorable ecological conditions for sexual reproduction, e.g.…”
Section: Introductionmentioning
confidence: 99%